The role of cyclin D1 and Ki‐67 in the development and prognostication of thin melanoma. Issue 3 (4th July 2020) - Kaufmann, Corina; Kempf, Werner; Mangana, Joanna; Cheng, Phil; Emberger, Michael; Lang, Roland; Kaiser, Andreas K; Lattmann, Evelyn; Levesque, Mitchell; Dummer, Reinhard; Koelblinger, Peter
Abstract : Aims: Despite their low individual metastatic potential, thin melanomas (≤1 mm Breslow thickness) contribute significantly to melanoma mortality overall. Therefore, identification of prognostic biomarkers is particularly important in this subgroup of melanoma. Prompted by preclinical results, we investigated cyclin D1 protein and Ki‐67 expression in in‐situ, metastatic and non‐metastatic thin melanomas. Methods and results: Immunohistochemistry was performed on 112 melanoma specimens, comprising 22  in situ, 48 non‐metastatic and 42 metastatic thin melanomas. Overall, epidermal and dermal cyclin D1 and Ki‐67 expression were semiquantitatively evaluated by three independent investigators and compared between groups. Epidermal Ki‐67 expression did not differ statistically in in‐situ and invasive melanoma ( P =  0.7). Epidermal cyclin D1 expression was significantly higher in thin invasive than in in‐situ melanoma ( P =  0.003). No difference was found in cyclin D1 expression between metastatic and non‐metastatic invasive tumours. Metastatic and non‐metastatic thin melanomas did not show significant differences in epidermal expression of Ki‐67 and cyclin D1 ( P =  0.148 and P =  0.611, respectively). In contrast, strong dermal expression of Ki‐67 was more frequent in metastatic than non‐metastatic samples (28.6 versus 8.3%, respectively, P =  0.001). The prognostic value of dermal Ki‐67 expression was confirmed by multivariate analysis ( P =  0.047). Conclusion: We found an increased expression of cyclin D1 in invasive thin melanomas compared to in‐situ melanomas, which supports a potential role of this protein in early invasion in melanoma, as suggested by preclinical findings. Moreover, our results confirm that high dermal Ki‐67 expression is associated with an increased risk of development of metastasis in thin melanoma and could possibly serve as a prognostic biomarker in clinical practice, especially if combined with additional methods.